Next-Generation Sequencing of 17 Genes Associated with Venous Thromboembolism Reveals a Deficit of Non-Synonymous Variants in Procoagulant Genes - Manderstedt, Eric; Lind-Halldén, Christina; Svensson, Peter; Zöller, Bengt; Halldén, Christer (Thrombosis and Haemostasis, 2019)
Background The heritability of venous thromboembolism (VTE) is only partially explained by variants in 17 previously VTE-associated genes.Objective This article screens for additional rare variants in the 17 genes and investigates the relative contributions of pro- and anticoagulant genes to VTE.Patients and Methods Ninety-six VTE patients from the population-based Malmö Thrombophilia Study were analysed using an AmpliSeq strategy and Ion Torrent sequencing and the variant data were compared with data from public databases.Results A total of 102 non-synonymous and 76 synonymous variants were identified. Forty-six non-synonymous variants were present in the human gene mutation database. Anticoagulant and procoagulant genes showed 14 and 22 rare non-synonymous variants, respectively. Individual patients showed varying numbers of risk factors; 13 patients had non-synonymous mutations in SERPINC1, PROC and PROS1 genes and 42 had factor V Leiden or prothrombin mutations generating a total of 47 patients with at least one of these risk factors. Ten common VTE-associated variants showed low level enrichments and no correlation to the other risk factors. The enrichment of previously identified risk factors was similar to previous studies. Determination of the nsyn/syn ratio (number of non-synonymous variants per non-synonymous site, nsyn, to the number of synonymous variants per synonymous site, syn) showed, as expected in patients, an increase of non-synonymous relative to synonymous anticoagulant variants compared with controls (nsyn/syn, 0.95 vs. 0.68). In contrast, non-synonymous procoagulant variants (nsyn/syn, 0.31 vs. 0.63) showed a decrease. We suggest that the deficit of non-synonymous variants in procoagulant genes is a novel mechanism contributing to VTE.
Keywords: venous thromboembolism; blood coagulation factors; anticoagulant; procoagulant; next-generation sequencing